PERSEPSI KEGUNAAN,KEMUDAHAAN,DAN RISIKO PADA APLIKASI M-BANKING BRI - Sefa Wardatul Aini, (2022)
The goal to be achieved in this study is to determine the results of the analysis of the perception of mobile banking application users towards the level of usability, convenience, and security of customers on the BRImo application. In this study using quantitative research. The method of data collection uses observation, surveys and literature studies. The sample in this study is people who have become BRI customers and use the BRImo application, which totals 35 respondents. The research model used in this study is descriptive quantitative in explaining statistically the level of perception of ease, usability, and security of BRImo users. The results showed that descriptive in each perception in the use of the BRImo application received a positive evaluation value. Perception of usability (Very Satisfied 25%, Satisfied 44%), Perception of Ease (Very Satisfied 26%, Satisfied 30%), and Perception of Security (Very Satisfied 30%, Satisfied 32%). Based on the results of the description, the perception of Mobile Banking users in using the BRImo application can be said to be satisfied.